Coaching educators: Impact of a novel national faculty development program for didactic presentation skills. Issue 3 (31st July 2021) - Jordan, Jaime; Yarris, Lalena M.; Dorfsman, Michele L.; Wolf, Stephen J.; Wagner, Mary J.
Abstract: Background: Didactic lectures remain common in medical education. Many faculty physicians do not receive formal training on public presentations or leading instructional sessions. Coaching has emerged in medical education with the potential to positively impact skills. We sought to evaluate a novel, national faculty peer‐coaching program created to improve lecture presentation skills and foster career development. Methods: This was a mixed‐methods study of participant and faculty perceptions after completing the Council of Residency Directors in Emergency Medicine Academy Coaching Program. Participants completed an online evaluative survey consisting of multiple choice and Likert‐type items. Program coaches participated in semistructured interviews. Descriptive statistics were reported for survey data. Thematic qualitative analysis by two independent reviewers was performed on interview data. Results: During 2012 to 2017, a total of 30 participants and 11 coaches from 37 residency programs across the United States engaged in the program. Twenty‐four (80%) participants completed the survey. Eight (73%) coaches participated in semistructured interviews. Data were collected between October and December 2018. The mean ± SD numbers of national presentations participants had given before and after the coaching program were 6.92 ± 7.68 and 16.42 ± 15.43, respectively. Since their coaching, most participants (87.5%) have been invited to give a lecture at another institution. Many participants felt that the program improved their lecture evaluations, public speaking, ability to engage an audience, and professional development. Almost all (92%) would recommend the program to a colleague. The coaches perceived multiple benefits including improved skills, self‐reflection, networking, career advancement, and personal fulfillment. Suggestions for improvement included improved administrative processes, more clear expectations, increased marketing, and increased participant and coach engagement. Conclusion: Participants and coaches perceived multiple benefits from this novel, national faculty coaching program. With identification of the success, challenges, and suggestions for improvement, others may benefit as they develop coaching programs in medical education.